Validity, acceptability, and procedural issues of selection methods for graduate study admissions in the fields of science, technology, engineering, and mathematics: a mapping review - Anastasia Kurysheva; Harold V. M. van Rijen; Cecily Stolte; Gönül Dilaver (SpringerOpen, 2023)
Abstract This review presents the first comprehensive synthesis of available research on selection methods for STEM graduate study admissions. Ten categories of graduate selection methods emerged. Each category was critically appraised against the following evaluative quality principles: predictive validity and reliability, acceptability, procedural issues, and cost-effectiveness. The findings advance the field of graduate selective admissions by (a) detecting selection methods and study success dimensions that are specific for STEM admissions, (b) including research evidence both on cognitive and noncognitive selection methods, and (c) showing the importance of accounting for all four evaluative quality principles in practice. Overall, this synthesis allows admissions committees to choose which selection methods to use and which essential aspects of their implementation to account for.